Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1097/01.lab.0000098429.59348.36
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inhibits Expression of Prolactin and Secretion of Cathepsin-D by the GH4C1 Pituitary Adenoma Cell Line

Abstract: SUMMARY:Diminished oxygen concentration within growing tumors may stimulate neovascularization by inducing both up-regulation of angiogenic factors and down-regulation of antiangiogenic agents. A potentially important molecule in the growth of pituitary adenomas is prolactin (PRL), which can be cleaved by cathepsin-D to yield a 16-kDa form (16K-PRL) with potent antiangiogenic effects. We examined the expression of PRL in cultured GH4C1 pituitary adenoma cells after exposure to hypoxia (0.1% oxygen) for periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 67 publications
2
9
0
1
Order By: Relevance
“…Also, the PRL levels of HA natives in this study are close to the levels observed in male Sherpas, with a mean concentration of 11.0 ng=dL (Bangham and Hackett, 1978). Hypoxia, in general, has been shown to inhibit the expression of PRL mRNA and protein in the GH4C1 lactotroph cell line (Cosío et al, 2003). Normal PRL levels in HA native men are indicative of an evolutionary adaptation to reproductive stress under extreme environment.…”
Section: Discussionsupporting
confidence: 61%
“…Also, the PRL levels of HA natives in this study are close to the levels observed in male Sherpas, with a mean concentration of 11.0 ng=dL (Bangham and Hackett, 1978). Hypoxia, in general, has been shown to inhibit the expression of PRL mRNA and protein in the GH4C1 lactotroph cell line (Cosío et al, 2003). Normal PRL levels in HA native men are indicative of an evolutionary adaptation to reproductive stress under extreme environment.…”
Section: Discussionsupporting
confidence: 61%
“…24 Then, down-regulation of PRL by hypoxia in GH4C1 cells supports the notion that hypoxia is an important factor for the hormonal moiety Figure 3A. Expressions of genes in hypoxia at 1% are compared with those at 21% oxygen by cDNA micro array analysis.…”
Section: Discussionmentioning
confidence: 57%
“…Cathepsin D cleaves PRL in the extracellular milieu of regressing corpus luteum [17] and mammary gland [16], and in cardiomyocytes under oxidative stress [13], conditions in which tissue remodelling and altered metabolic activity can acidify the pericellular pH. Cultured GH4C1 pituitary adenoma cells also secrete cathepsin D, and mimicking the tumor microenvironment by exposure to hypoxia reduces its release [26], suggesting that extracellular production of vasoinhibins could be decreased and favor the proangiogenic condition necessary for prolactinoma growth.…”
Section: Generation Of Endogenous Vasoinhibinsmentioning
confidence: 94%